Kosovo Social Assistance Scheme Study : Assessment and Reform Options - World Bank Group (World Bank, Washington, DC, 2019)
The Social Assistance Scheme (SAS) is the main social assistance program in Kosovo and the sole program targeted at poverty reduction in Kosovo and, importantly, the only program in which household income and assets are used to identify beneficiaries. In the absence of SAS, the overall poverty gap would have been 1.8 percentage points higher in 2016, and the poverty rate would have been 1.5 percentage points higher. Yet, the importance of SAS in Kosovo’s social protection system has declined; decreases in spending on targeted social assistance in Kosovo goes against a worldwide trend. The Government of Kosovo seeks to reform the SAS to eliminate discrimination in program design, promote inclusion and reduce poverty. This report reviews the main design criteria of the SAS, its performance in international comparison, and provides directions for reform based on simulations with household survey data.